Performance Monitoring in Medication-Naïve Children with Tourette Syndrome - Eichele, Heike; Eichele, Tom; Bjelland, Ingvar; Høvik, Marie F.; Sørensen, Lin; van Wageningen, Heidi; Worren, Marius Kalsås; Hugdahl, Kenneth; Plessen, Kerstin J. (Frontiers in Neuroscience, 2016)
Background: Tourette syndrome (TS) is a childhood-onset neurodevelopmental disorder and its impact on cognitive development needs further study. Evidence from neuropsychological, neuroimaging and electrophysiological studies suggest that the decline in tic severity and the ability to suppress tics relate to the development of self-regulatory functions in late childhood and adolescence. Hence, tasks measuring performance monitoring might provide insight into the regulation of tics in children with TS. Method: Twenty-five children with TS, including 14 with comorbid Attention-deficit/hyperactivity disorder (ADHD), 39 children with ADHD and 35 typically developing children aged 8-12 years were tested with a modified Eriksen-Flanker task during a 34-channel electroencephalography (EEG) recording. Task performance, as well as stimulus-locked and response-locked event-related potentials (ERP) were analyzed and compared across groups. Results: Participants did not differ in their behavioral performance. Children with TS showed higher amplitudes of an early P3 component of the stimulus-locked ERPs in ensemble averages and in separate trial outcomes, suggesting heightened orienting and/or attention during stimulus evaluation. In response-locked averages, children with TS had a slightly higher positive complex before the motor response, likely also reflecting a late P3. Groups did not differ in post-response components, particularly in the error-related negativity (ERN) and error-related positivity (Pe). Conclusions: These findings suggest that children with TS may employ additional attentional resources as a compensatory mechanism to maintain equal behavioral performance.